A comparison of conscious sedation and local anesthesia for thrombectomy in acute ischemic stroke: a multicenter study - Onalan, Aysenur; Gurkas, Erdem; Akpinar, Cetin Kursad; Aykac, Ozlem; Acar, Turkan; Acar, Bilgehan; Ozdemir, Atilla Ozcan (Frontiers Media Sa, 2024)
Introduction Ischemic cerebrovascular disease (ICVD) is a serious health problem in which brain tissue suffers from hypoxic damage due to obstruction in cerebral vessels. Mechanical thrombectomy is a commonly used method in the treatment of these patients. However, the effects of local anesthesia (LA) and conscious sedation (CS) during thrombectomy are still unclear. We evaluated whether there was a relationship between the two anesthesia regimens in terms of 90-day modified Rankin Scale (mRS) scores.Methods In this study, a retrospective observational study was conducted to evaluate the effects of LA and CS used during mechanical thrombectomy in four comprehensive stroke centers among ICVD patients. Patients were divided into the LA group and the CS group. Statistical analysis was performed before and after 1:1 matching under propensity score matching (PSM) analysis. The primary outcome measure was an mRS score of 0-2 at 90 days. Secondary outcomes were procedure times, recanalization rates, symptomatic and asymptomatic hemorrhage rates, and procedural complications.Results A total of 193 patients (118 patients with LA and 75 patients with CS) were included in the final analysis before PSM. After 1:1 PSM, 98 patients-49 patients from each group-were included in the study. There was no difference in clinical outcomes between the LA- and CS-applied groups (p = 0.543). When blood pressure (BP) values at follow-up after endovascular treatment (EVT) were compared, the lowest systolic and lowest diastolic BP were found to be lower in the CS group (p = 0.001 and p = 0.009). There was no significant difference between the two groups in terms of recanalization rates, symptomatic intracranial hemorrhage (sICH) rates, 90-day mRS, and procedure-related complication rates (p = 0.617, p = 0.274, p = 0.543, and p = 1.000).Conclusion This study did not reveal the superiority of CS applied during EVT on 90-day mRS, sICH, recanalization rates, or procedural complications. However, the risk of developing hypotension during the CS application was found to be high.
Keywords: conscious sedation; local anesthesia; endovascular treatment; large vessel occlusion; propensity score matching